SMEs in services trade: A GATS perspective - Rudolf Adlung; Marta Soprana (World Trade Organization (WTO), 2012)
Issues related to small- and medium-sized enterprises (SMEs) supplying services have been raised at earlier stages of the Doha Round in various negotiating contexts and, more recently, at meetings of the Council for Trade in Services. It is difficult, however, to find a common denominator as to whether SME-related concerns might merit attention, from a trade policy perspective, under the General Agreement on Trade in Services (GATS). Without proposing any priorities, this paper seeks to provide an overview of issues that Members might want to address in the WTO, from promoting compliance with transparency disciplines under existing provisions to advancing the liberalization and rule-making mandates of the GATS with an SME focus.
Keywords: F13; F53; L16; 330; Trade in Services; GATS; small- and medium-sized enterprises; GATS; Internationaler Dienstleistungsverkehr; Handelsliberalisierung; KMU; Welt